Quantifying Soil Water and Root Dynamics Using a Coupled Hydrogeophysical Inversion - Kuhl, A.S. (2020)
In this study, we developed and tested a coupled hydrogeophysical inversion approach that uses electrical resistivity data to estimate soil hydraulic, petrophysical, and root dynamic parameters. This builds on prior research that used either a coupled hydrogeophysical inversion to estimate soil hydraulic parameters only, or a hydrological inversion to estimate root distribution or root water uptake parameters. Our results indicate that under the conditions tested, this approach accurately captures root water dynamics and soil hydraulic parameters. This opens up opportunities to noninvasively image a variety of root distributions and soil systems, better understand the dynamics of RWU processes, and improve estimates of transpiration for systems models.